Assessing The Impact of Covid-19 on Energy Sector Performance in the Asia-Pacific - RR Patricia Prinza Prameswari; Vina Nugroho (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study explores the effects of the COVID-19 pandemic on the performance of energy sector companies, focusing on how the pandemic interacts with company characteristics—such as size, liquidity, and capital structure— impacting Return on Assets (ROA), which is used as a key measure of company performance. It further distinguishes between fossil fuel and alternative energy sectors, as well as between companies in developed and emerging markets, to assess whether the pandemic's effects varied across these categories. The analysis utilizes unbalanced panel data from publicly listed energy firms in the Asia Pacific region from 2013 to 2023. The results reveal that the fossil fuel sector experienced a sharper decline in performance compared to the alternative energy sector during the pandemic. Additionally, significant differences emerged between energy companies in developed and emerging markets; firms in developed markets, benefiting from larger sizes, higher liquidity, and sufficient cash reserves, were generally better equipped to withstand the pandemic's challenges.